Perspectives of women from migrant and refugee backgrounds accessing the Cross Cultural Worker Service in maternity and early childhood services—a qualitative study - Helen J. Rogers; Caroline S. E. Homer; Caroline S. E. Homer; Amanda Henry; Amanda Henry; Amanda Henry (Frontiers in Global Women's Health)
IntroductionWomen from migrant and refugee backgrounds living in high-income countries have an increased risk of adverse perinatal outcomes and lower satisfaction with healthcare. A Cross Cultural Workers (CCWs) Service was implemented in Sydney, Australia, supporting women and families throughout pregnancy to their child being 5 years old.MethodsThis study aimed to describe women's experience of the CCW Service and recommendations for improvement using interviews at 6 or 12 months postpartum. A framework approach was used for analysis.ResultsFour themes were generated from 23 interviews; (1) gaining knowledge, (2) strengthening capacity, (3) providing support; and (4) sharing culture, language, and migration journey. The impact of COVID-19 was a cross-cutting issue.DiscussionThe CCW Service was highly regarded, helpful, informative, and enhanced women's care experience. Recommendations for improvement were increased CCW workforce and provision of group education. This model has the potential to improve perinatal care of women from migrant and refugee backgrounds.